A Chromium Hydroxide/MIL‐101(Cr) MOF Composite Catalyst and Its Use for the Selective Isomerization of Glucose to Fructose. (23rd March 2018) - Guo, Qiang; Ren, Limin; Kumar, Prashant; Cybulskis, Viktor J.; Mkhoyan, K. Andre; Davis, Mark E.; Tsapatsis, Michael
Abstract: A metal–organic framework (MOF)‐based catalyst, chromium hydroxide/MIL‐101(Cr), was prepared by a one‐pot synthesis method. The combination of chromium hydroxide particles on and within Lewis acidic MIL‐101 accomplishes highly selective conversion of glucose to fructose in the presence of ethanol, matching the performance of optimized Sn‐containing Lewis acidic zeolites. Differently from zeolites, NMR spectroscopy studies with isotopically labeled molecules demonstrate that isomerization of glucose to fructose on this catalyst, proceeds predominantly via a proton transfer mechanism.